Examining the Impact of Burnout on Hospital Nurses Engaged in Shift Work: Insights From a Nationwide Cross-Sectional Study in Malaysia - Kun Yun Lee DrPH, MPH, MBBChBAO; Nursyahda Zakaria MSc, BSc; Norhaniza Zakaria MD (SAGE Publishing, 2024)
Introduction Shift workers follow nonstandard schedules that encompass overnight duty, rotational timetables, or permanent night work which can lead to misaligned core circadian physiology. Shift work has been associated with sleep deprivation, burnout, and metabolic syndrome among healthcare workers. Objective We aimed to examine if shift nurses working in Malaysian public hospitals are more predisposed to burnout and to determine the predictors of burnout in this profession. Method This national-level cross-sectional study was conducted among nurses in public hospitals in Malaysia between July and November 2019 using self-administered questionnaires. Maslach Burnout Inventory-Human Service Survey was used to determine burnout. Multistage stratified sampling was used to recruit nurses from 32 hospitals. A complex sampling analysis was performed. Results Among the 1,491 hospital nurses, more than half (70.8%) of them followed shift work schedules. Shift nurses were mostly below 40 years old (80.9%), diploma holders (87.2%), and of lower professional grades (64.2%). The prevalence of overall burnout, as well as the domains of emotional exhaustion and depersonalization, was higher among shift nurses (27.1%) as compared to their counterparts (22.4%). Nurses who performed more than six night shifts per month were 2.6 times more predisposed to burnout. Conclusion Shift work is integral to ensure round-the-clock nursing care for patients. However, nurses are increasingly faced with more shift duties due to heavy patient loads and staff shortages. Modified work schedules must be implemented to provide sufficient rest time for shift nurses to mitigate burnout. Additionally, proper human resource projection and distribution are imperative to prevent worsening burnout.